168 Impact of morbidity and mortality conferences on the incidence of adverse events in an intensive care unit (ICU). (23rd September 2015) - Misset, Benoît; Bruel, Cédric; Touati, Samia; Dumain, Martine; Moulard, Marie-Luce; Philippart, François; Garrouste-Orgeas, Maïté; Carlet, Jean
Abstract : Context and objectives: Mortality is the principal indicator used to assess the performance of Intensive Care Units (ICU), through the ratio between observed and predicted mortality with the Simplified Acute Physiology Score II (SAPS II) at admission, called Standardised Mortality Ratio (SMR). The differences in case-mix make it difficult to compare two ICUs with the SMR only, and the progressive improvement of the prognosis due to medical progress make historical comparisons difficult to perform within a single ICU. The incidence of several well defined and supposedly avoidable adverse events is another marker of quality of care. The aim of the study was to assess the impact of morbidity and mortality conferences (MMC) on adverse events in our ICU. Program: The follow-up of several adverse events has been performed prospectively in our ICU since 2000, on patients with a ICU length of stay over 48 h. We implemented MMC in 2003 according to methods similar to the ones currently promoted by the French Authority for Health. The files of all the patients deceased in the ICU are analysed. The meetings take place every 6 weeks. The intensive care physicians and the interns are invited to participate. The conclusions of the sessions are recorded in an electronic database. The cases in which the treatment was considered inadequate or associated with an adverse event led to adjustment of existing procedures. The adverse events which were used as indicators in the entire population were accidental removal of the tracheal tubes and secondary pneumothoraces, on an electronic database, prospectively completed for all patients hospitalised for more than 48 h, except during the summer months of vacations. Results: Among 486 deceased patients, 406 stays were analysed (83%). The therapy was considered inadequate or associated with an adverse event in 61 patients (15%). The adverse event played a significant role in the death in 22 patients (6%) and was considered avoidable in 21 (6%). It both played a significant role and was considered avoidable in 11 patients (3%). The principal adverse events in the patients discussed during a MMC were pneumothorax (n=13), haemorrhage (n=9), accidental removal or difficult placement of tracheal tube (n=9), cardiac arrest (n=8) and drug allergy or overdose (n=8). During the study period, in the entire admitted population, the incidence of accidental removal or difficult placement of the tracheal tube decreased progressively from 14% to 8% and the incidence of secondary pneumothoraces from 4% to 1%. The ratio between observed and predicted mortality decreased from 1.05 to 0.6. Discussion: The causal relationship between MMC implementation and the decrease in adverse events is likely. However, other aspects of the quality culture of our ICU may have played a role. The main technical limitations of our study were the absence of measurement of the compliance to the procedures, and the impossibility to measure the adverse events exhaustively. Conclusion: The prospective analysis of the causes of death in our ICU was associated with a reduction of the adverse events occurring in our entire population. Contexte et objectifs: La mortalité est le principal indicateur pour mesurer la performance des services de réanimation, au travers du rapport entre mortalité observée et mortalité prédite par le score SAPS II à l'admission ou Standardised Mortality Ratio (SMR). Les différences de case mix rendent impossibles la comparaison entre deux services avec le seul SMR, et l'amélioration progressive du pronostic au cours des années grâce aux progrès médicaux rendent difficiles les comparaisons historiques au sein d'un même service. L'incidence de certains événements iatrogènes bien définis et supposés évitables est un autre marqueur de la qualité des prises en charge. Le but de ce travail a été d'évaluer l'impact des revues de morbi-mortalité sur la iatrogénie dans notre service de réanimation. Programme: Le suivi de certains événements indésirables est effectué dans notre service depuis 2000 chez tous les patients ayant une durée de séjour supérieure à 48H. Nous avons implanté des RMM en 2003 selon une méthodologie similaire à celle qui est proposée actuellement par la HAS. Les dossiers sont analysés pour tous les patients décédés dans le service. Les réunions ont lieu toutes les 6 semaines. Les médecins réanimateurs et les internes participent aux réunions. Les conclusions des séances sont archivées sur une base de données informatique. Les cas pour lesquels le traitement a été jugé imparfait ou associé à un événement iatrogène, ont été colligés et aboutis à l'adaptation des procédures existantes. Les événements iatrogènes suivis sur l'ensemble de la population sont les extubations accidentelles et les pneumothorax secondaires, au moyen d'une base de données informatisée, renseignée prospectivement. Ce recueil est effectué chez les patients hospitalisés plus de 48H, en dehors de la période estivale de congés. Résultats: Parmi les 486 patients décédés, 406 séjours ont été analysés (83%). Le traitement a été jugé imparfait ou iatrogène chez 61 patients (15%). L'événement iatrogène a joué un rôle significatif dans le décès chez 22 patients (6%) et a été jugé évitable chez 21 patients. Il a joué un rôle significatif et été jugé évitable de façon simultanée chez 11 patients (3%). Les principaux événements iatrogènes dans la population analysée au cours de RMM, les événements iatrogènes ont été un pneumothorax (N=13), une hémorragie (N=9), une extubation accidentelle ou une difficulté d'intubation (N=9), un arrêt cardiaque (N=8) et une allergie ou un surdosage médicamenteux (N=8). Pendant la période d'étude dans l'ensemble de la population du service, l'incidence des extubations accidentelles est passée progressivement de 14% à 8% et l'incidence des pneumothorax de 4% à 1%. Le rapport entre mortalité observée et mortalité prévisionnelle est passée de 1, 05 à 0, 6. Discussion: La relation de cause à effet entre l'implantation des RMM et la diminution de la iatrogénie est probable. D'autres aspects de la culture de la qualité ont cependant pu jouer un rôle. Les principales limites techniques de notre étude ont été l'absence de mesure de la compliance aux procédures, et l'impossibilité de mesurer les événements iatrogènes de façon exhaustive. Conclusion: L'analyse prospective des causes des décès survenant dans notre service de réanimation semble avoir participé à la réduction des événements iatrogènes survenant dans l'ensemble de notre population.